PENERAPAN PRINSIP HIGIENE SANITASI DENGAN KEBERADAAN HAZARD BIOLOGIS PADA PERALATAN DI KANTIN UNIVERSITAS - Musfirah Musfirah; Atikah Rahayu; Helfi Agustin (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2022)
Cafetaria in university must meet the nutritious and healthy snacks for students. The quality of healthy and nutritious food is influenced by hygienic, good sanitation and free-hazard contamination aspects on the canteen management. Poor sanitation and hygiene utensils and storage management can increase food contamination.This study aimed to determine the association of implementation of food and hygiene sanitation with the biological hazard on eating utensils. This study used cross-sectional design  and  was conducted in May 2017. The number of canteen sample were 9 canteen and 15 food handlers. The data were collected by microbiological quality checks on tableware and cookware which were often used by the food handlers in food management, observation sheet of sanitary conditions of eating utensils, and questionnaires to find out the implementation of food sanitation hygiene in the canteen. The analytical statistic method used Fisher test. The results study indicate the implementation of hygiene sanitation principle was not associated  with the existence of biological hazard of germs in  tableware (p = 0,538) and cookware (p = 0,476) variable. Knowledge and practice of food safety needs to be increased through training on food security and food sanitation hygiene among food handlers.